ANALISIS KEBIJAKAN INDONESIA DALAM MENGATASI HAMBATAN EKSPOR SUMBER DAYA IKAN TCT (TUNA-CAKALANG-TONGKOL) KE PASAR JEPANG. - Noval Adi Priyatno (2022)
Indonesia is an archipelagic country with abundant fisheries resources in it. One of these fishery resources is Tuna-Cakalang-Tongkol (TCT). TCT fish is one of the leading export products, with one of the destination countries being Japan., Japan is a country with a high number of fish consumption, besides that the historical factors of Indonesia and Japan in establishing international relations have existed for quite a long time. Therefore, Japan has become one of the destination countries for TCT fish exports, but there are several obstacles that occur in the cooperation. The Indonesian government tries to implement various policies in overcoming the existing Barriers. Descriptive qualitative research is a method taken to unravel the phenomenon of these obstacles, with the aim of research to analyze Indonesian policies to overcome barriers to TCT fish exports in the Japanese market by using the theory of Bilateral Cooperation and Trade Diplomacy as the basis for the analysis of these policies. Where the results of the study show that there are 3 forms of internal barriers and 2 forms of external barriers in maximizing the cooperation of Indonesian and Japanese TCT fish. In overcoming these obstacles, the Indonesian government made 4 policies with the help of the KKP in their implementation.